2022
DOI: 10.1007/s40534-022-00283-0
|View full text |Cite
|
Sign up to set email alerts
|

Mud pumping in high-speed railway: in-situ soil core test and full-scale model testing

Abstract: Mud pumping induced by moving train loads on rainwater-intruded roadbed causes intensive track vibrations and threatens safety of high-speed trains. In this paper, a vehicle–track–subgrade finite element model was established to analyze the dynamic responses of a ballastless track, and results showed that the concrete base and roadbed were detached because of the whipping effect arising from the rainwater intrusion channel. An in-situ soil core test showed that the intruded rainwater accumulated in roadbed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Number of days with maximum temperature exceeding 35 degrees celsius : This data can serve as an indicator reflecting extreme high temperatures 16 .…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Number of days with maximum temperature exceeding 35 degrees celsius : This data can serve as an indicator reflecting extreme high temperatures 16 .…”
Section: Methods and Datamentioning
confidence: 99%
“…The findings revealed that the frost heave rate was influenced by the initial water content before freezing and the replenishment of moisture during the freezing process. Wan et al (2022) established a vehicle-track-subgrade vertical dynamic coupled analysis model was established using ABAQUS 16 . The study found that debonding easily occurred between the end of the base plate and the surface of the subgrade.…”
Section: Introductionmentioning
confidence: 99%
“…4 Typical water-induced subgrade defects, including mud pumping and differential settlement, may occur. 5,6 These defects can weaken the support ability of the subgrade to slab track, causing the deterioration of the track geometry and thus bringing a potential threat to the operation safety of HSR trains. 7 When the track undergoes such problems, the HSR trains may need to reduce the operation speed, which leads to a decrease in the operation efficiency.…”
Section: Introductionmentioning
confidence: 99%